Effects of Trichoderma sp. on the pea (Pisum sativum L.) growth and development (2014)
It is estimated that the cultivation of pea generates about 2.3 million wages and about 15,000 direct jobs, from which depend more than 26,000 producers (1). In the absence of alternative production, the farmer has traditionally made use of synthetic chemical products, practice which is becoming more restricted for economic and ecological reasons, affecting negatively the population (2). So we need to find new production models that contribute to improve the life quality of the farmers who depend on the crop. This work determined the effects of the Trichoderma sp. application on the pea growth and development. The Trichoderma sp. native strain was isolated from soil of the pea crop.Then there were carried out Trichoderma sp. dilutions, in both the native and commercial plants, Afterwards the plants were inoculated and measured the variables of growth, development and germination, such as plant height, number of stems, disease incidence, leaf area, fresh weight of root and aerial part dry weight of root and aerial part, root length. Therefore the application of Trichoderma in commercial pea crop, significantly improves the growth and development of this culture, influencing its physiological variables such as germination, leaf area, root dry weight, root fresh weight, dry weight of the aerial parts, fresh weight shoot and root length.